Chronic Nicotine Exposure Induces Murine Aortic Remodeling and Stiffness Segmentation—Implications for Abdominal Aortic Aneurysm Susceptibility - Wagenhäuser, Markus U.; Schellinger, Isabel N.; Yoshino, Takuya; Toyama, Kensuke; Kayama, Yosuke; Deng, Alicia; Guenther, Sabina P.; Petzold, Anne; Mulorz, Joscha; Mulorz, Pireyatharsheny; Hasenfuß, Gerd; Ibing, Wiebke; et al. (Frontiers in Physiology, 2018)
Aim: Arterial stiffness is a significant risk factor for many cardiovascular diseases, including abdominal aortic aneurysms (AAA). Nicotine, the major active ingredient of e-cigarettes and tobacco smoke, induces acute vasomotor effects that may temporarily increase arterial stiffness. Here, we investigated the effects of long-term nicotine exposure on structural aortic stiffness. Methods: Mice (C57BL/6) were infused with nicotine for 40 days (20mg/kg/day). Arterial stiffness of the thoracic (TS) and abdominal (AS) aortic segments was analyzed using ultrasound (PWV, pulse wave velocity) and ex vivo pressure myograph measurements. For mechanistic studies, aortic matrix-metalloproteinase (MMP) expression and activity as well as medial elastin architecture were analyzed. Results: Global aortic stiffness (PWV) increased with nicotine. In particular, local stiffening of the abdominal segment occurred after 10 days, while thoracic aortic stiffness was only increased after 40 days, resulting in aortic stiffness segmentation. Mechanistically, nicotine exposure enhanced expression of MMP-2/-9 and elastolytic activity in both aortic segments. Elastin degradation occurred in both segments, however basal elastin levels were higher in the thoracic aorta. Finally, MMP-inhibition significantly reduced nicotine-induced MMP activity, elastin destruction, and aortic stiffening. Conclusion: Chronic nicotine exposure induces aortic MMP expression and structural aortic damage (elastin fragmentation), irreversibly increasing aortic stiffness. This process predominantly affects the abdominal aortic segment, presumably due in part to a lower basal elastin content. This novel phenomenon may help explain the role of nicotine as a major risk factor for AAA formation and has health implications for e-cigarettes and other modes of nicotine delivery.